PUBLIC POLICY INNOVATION IN PROMOTING INCLUSIVE ECONOMIC GROWTH IN THE DIGITAL TRANSFORMATION ERA - Mohammad Muzaki; Mohammad Fauzil Adhim (International Conference on Humanity Education and Society (ICHES), 2025)
Digital transformation has become a major force in reshaping governance and public service systems. Public policy innovation plays a crucial role in improving bureaucratic efficiency, enhancing transparency, and promoting the creation of an inclusive economy that is responsive to the needs of society. This study aims to analyze the role of policy innovation in fostering inclusive economic growth in the digital era, with an emphasis on the implementation of digital bureaucracy systems such as e-budgeting, e-planning, and e-procurement. This research employs a descriptive qualitative approach based on a literature review of academic sources, policy reports, and government institutional data. The findings indicate that the use of technology and data in policy formulation has accelerated the transformation of public services, expanded citizen participation, and improved the accuracy of social interventions targeting marginalized groups. Moreover, data-driven policy approaches and open government practices have been shown to strengthen public trust and policy accountability. Nevertheless, challenges such as the digital divide,limited digital literacy, and unequal access to infrastructure still need to be addressed in the implementation of inclusive policies. This study recommends strengthening cross-sector collaboration and enhancing local capacity as key strategies to achieve fair and sustainable economic growth in the digital transformation era